A novel mutation of the hGR gene causing Chrousos syndrome. (14th July 2015) - Nicolaides, Nicolas C.; Geer, Eliza B.; Vlachakis, Dimitrios; Roberts, Michael L.; Psarra, Anna‐Maria G.; Moutsatsou, Paraskevi; Sertedaki, Amalia; Kossida, Sophia; Charmandari, Evangelia
Abstract Background Natural mutations in the human glucocorticoid receptor (hGR, NR3C1) gene cause Chrousos syndrome, a rare condition characterized by generalized, partial, target‐tissue insensitivity to glucocorticoids. Objective To present a new case of Chrousos syndrome caused by a novel mutation in the hGR gene, and to elucidate the molecular mechanisms through which the natural mutant receptor affects glucocorticoid signal transduction. Design and Results The index case presented with hirsutism, acne, alopecia, anxiety, fatigue and irregular menstrual cycles, but no clinical manifestations suggestive of Cushing's syndrome. Endocrinologic evaluation revealed elevated 08:00 h plasma adrenocorticotropic hormone, serum cortisol and androstenedione concentrations and increased urinary free cortisol excretion. The patient harbored a novel A > G transition at nucleotide position 2177, which resulted in histidine (H) to arginine (R) substitution at amino acid position 726 of the receptor (c.2177A > G, p.H726R). Compared with the wild‐type receptor, the mutant receptor hGRαH726R demonstrated decreased ability to transactivate glucocorticoid‐responsive genes and to transrepress the nuclear factor‐κB signalling pathway, displayed 55% lower affinity for the ligand and a four‐fold delay in nuclear translocation, and interacted with the glucocorticoid receptor‐interacting protein 1 coactivator mostly through its activation function‐1 domain. Finally, a 3‐dimensional molecular modelling study of the H726R mutation revealed a significant structural shift in the rigidity of helix 10 of the receptor, which resulted in reduced flexibility and decreased affinity of the mutant receptor for binding to the ligand. Conclusions The natural mutant receptor hGRαH726R impairs multiple steps of glucocorticoid signal transduction, thereby decreasing tissue sensitivity to glucocorticoids.